Dampak Sosial Budaya Pro-Poor Tourism: Social Humanity Tour Di Jakarta - Lestari, Dita Ayu; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA, 2019)
The background of this research begins when one travel agent in Jakarta provides a tour package based on Pro-Poor Tourism called Social Humanity Tour. In Social Humanity Tour tourists will be invited to see people’s lives, interact and conduct social activities in the slum area in Jakarta. Kampung Tongkol and Kampung Luar Batang are the most visited destinations for tourists. The purpose of this research is to know the socio-cultural impact of Pro-Por Tourism in Kampung Tongkol and Kampung Luar Batang based on the Social Humanity Tour. Data collection in this research is done through observation,interview, and documentation. The method used in this research is qualitative method and the collected data is analyzed using the descriptive qualitative method. The result obtained in this research regarding the changes in the form of community in Kampung Tongkol and Kampung Luar Batang is that there is a positive change. From 9 aspects of socio-cultural impacts used in the research, there are only 2 aspect that have changed in both villages. Communities become open-minded towards the tourism, the community becomes braver while interacting with tourists, and the community,especially the children, receives many benefits both in the material and non-material form. In addition tourists often educate the children there. Some suggestions that must be considered in this research is, that the communities should not be oriented with material assistance from tourists because it can threaten the sustainability of the tourism in both villages. Keyword : Alternative Tourism, Pro-Poor Tourism, Social Humanity Tour